Effect of Nanobubble Technology Gamal Leaf POC on Pakcoy (Brassica rapa L.) Quality in Hydroponic - Tazri, Mufidah Insani; Fevria, Resti; Vauzia, Vauzia; Razak, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pakcoy (Brassica rapa L.) production in Indonesia has declined due to limited land and reliance on costly inorganic fertilizer such as ABmix. Therefore, alternative fertilizer that are more efficient and enviromentally friendly are needed. This study aimed to eximine the effects of the liquid organic fertilizer (POC) made from gamal leaves (Gliricidia sepium Jacq. Kunth) using nano bubble technology on the growth and quality of pakcoy in a hydroponic system. A Completely Randomized Design (CRD) was used with five treatments: P1 (100% ABmix), P2 (75% ABmix +25% POC nano), P3 (50% ABmix+50% POC nano), P4 (25% ABmix+75% POC nano), and P5 (100% POC nano) each replicated five times. Observed parameters included plant height, leaf number and area, and fresh and dry weight. Result showed that treatment P3 gave the best performance in all observed variables. The balanced combination of ABmix and POC nano improve nutrient availability and photosynthetic efficiency, supporting optimal plant growth. Nano POC from gamal leaves shows potential as an alternative organic fertilizer in hydroponic systems, though further research is needed to understand its long-term effects and broader application.